Sistem Pakar Mendiagnosa Penyakit Gigi Anak Usia Satu Sampai Lima Tahun Menggunakan Metode Certainty Factor - Razi, Fahrul (Jurnal Teknologi Informasi (JUTECH), 2022)
Teeth are one of the most important organs as a digestive tool for the human body. Therefore the teeth must be treated as well as possible. If no treatment is taken, the disease will cause the teeth to become infected. Dental diseases in one-to-five-year-olds most often seen are dental caries and gingivitis. Dental Caries can also be called cavities. While Gingivitis is a disease of tartar and gum inflammation. Expert System is an information system that contains the knowledge of an expert so that it can be used for consultation. In the expert system there are several methods, one of which is Certainty Factor. Cerainty Factor is one technique used to overcome uncertainty in decision making.